Heuristic optimization approaches for capacitor sizing and placement: A case study in Kazakhstan - CEYLAN, OĞUZHAN (My University, 2022)
Two methods for estimating the near-optimal positions and sizes of capacitors in radial distribution networks are presented. The first model assumes fixed-size capacitors, while the second model assumes controllable variable-size capacitors by changing the tap positions. In the second model, we limit the number of changes in capacitor size. In both approaches, the models consider many load scenarios and aim to obtain better voltage profiles by minimizing voltage deviations and active power losses. We use two recently developed heuristic algorithms called Salp Swarm Optimization algorithm (SSA) and Dragonfly algorithm (DA) to solve the proposed optimization models. We performed numerical simulations using data by modifying an actual distribution network in Almaty, Kazakhstan. To mimic various load scenarios, we start with the baseline load values and produce random variations. For the first model, the optimization algorithms identify the near-optimal positioning and sizes of fixed-size capacitors. Since the second model assumes variable-size capacitors, the algorithms also decide the tap positions for this case. Comparative analysis of the heuristic algorithms shows that the DA and SSA algorithms give similar results in solving the two optimization models: the former gives a slightly better voltage profile and lower active power losses.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Engineering and Technology; ENERJİ VE YAKITLAR; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENERGY & FUELS; ENGINEERING; Engineering, Computing & Technology (ENG); Enerji Mühendisliği ve Güç Teknolojisi; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Genel Mühendislik; Genel Enerji; Mühendislik (çeşitli); Yakıt Teknolojisi; Enerji (çeşitli); Fizik Bilimleri; Energy Engineering and Power Technology; Renewable Energy, Sustainability and the Environment; General Engineering; General Energy; Engineering (miscellaneous); Fuel Technology; Energy (miscellaneous); Physical Sciences; smart grid; optimization; capacitor allocation and sizing problem; heuristic methods; DISTRIBUTION-SYSTEMS; OPTIMAL ALLOCATION; POWER LOSS; SWITCHED-CAPACITOR; SHUNT CAPACITORS; ALGORITHM; LOCATION; VOLTAGE; smart grid; optimization; capacitor allocation and sizing problem; heuristic methods